Analysis Of Break Even Point (BEP) At Khair Laundry In Pontianak City - Yuli Santika; Muhliyanto Muhliyanto; Bela Bela; Mirdawati Mirdawati; Matsna Marwan Addin (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2024)
Laundry is a cleaning business that cleans dirty clothes so they can be sent. This business is very promising because the demand for this service is quite high. This research aims to determine the break-even point for khair laundry to make a profit. This research was carried out at laundry service MSMEs in Pontianak. This research uses primary data obtained from direct interviews with the owner of Khair laundry. Secondary data is generated from records made by the khair laundry service business. This research is descriptive research using quantitative data where the data was obtained through interview methods with business owners. The data obtained is in the form of selling price per unit (p), recording the number of kg of laundry that comes in for 1 month, building rental costs, equipment, operational costs, employee salary costs and packaging costs. Based on research results, the average kg of laundry produced per month is 860,012 kg, with fixed costs of Rp. 800,000 and variable costs per kg Rp. 4,000. Based on the laundry price per kg Rp. 6,000, then the number of kg of laundry produced to reach the break-even point (BEP) in one month is 400 kg.